Intramolecular interaction suggests an autosuppression mechanism for the innate immune adaptor protein MyD88. Issue 87 (9th October 2018) - Uno, Masatoshi; Watanabe-Nakayama, Takahiro; Konno, Hiroki; Akagi, Ken-ichi; Tsutsumi, Naotaka; Fukao, Toshiyuki; Shirakawa, Masahiro; Ohnishi, Hidenori; Tochio, Hidehito
Abstract : An autosupression of MyD88 is regulated by the intramolecular interaction between TIRMyD88 and DDMyD88 . Abstract : MyD88 (myeloid differentiation factor 88) is an important protein in innate immunity. Two structural domains of MyD88 have been well characterized separately, but the global architecture of full-length MyD88 remained unclear. Here, we propose an autosuppressive mechanism of MyD88 regulated by the intramolecular interaction between the two domains.